Female Education, Contraceptive Use, and Fertility: Evidence from Uganda - Bbaale, Edward; Mpuga, Paul (Consilience, 2011)
We use the Demographic and Health Survey of 2006 to examine the relationship between female education, contraceptive use, and fertility rates in Uganda. Our findings reveal that female education, especially at the secondary and post-secondary levels, increases the likelihood of using contraceptives and reduces fertility. As a result, measures that aim to educate women beyond secondary level are needed. The government programme to extend free education at the secondary level is an important measure that may help to reduce fertility and should therefore be strengthened.